Indonesian Students’ Cross-Cultural Adaptation in Busan, Korea - Deddy Mulyana; Bertha Sri Eko (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2017)
This study aims to explore the cross-cultural adaptation of Indonesian students in Busan, South Korea. It uses a qualitative approach based on the U-curve (a four-stage model of cross-cultural adjustment consisting of the phases of honeymoon, crisis, recovery and adjustment). It involves in-depth interviews with 10 Indonesian students in Busan. The study found that the U-Curve model of cross-cultural adaptation is still useful. In the context of the informants’ experiences, it is characterized by the main barriers that include differences in language and values of friendship, cross-cultural stereotypes and prejudices that led to discrimination. The study also identified culture shock faced by some of the informants as well as their coping strategies.